PENGARUH UPAH MINIMUM DAN TINGKAT PENGANGGURAN TERHADAP JUMLAH PENDUDUK MISKIN DI PROVINSI JAWA TIMUR - Sholihin, M. Khoirus; wiwoho, bambang (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2020)
The influence of the minimum wage and unemployment rate on the number of poor people in East Java Province still needs to be considered because poverty is a global humanitarian problem and is still a central issue in any part of the world. Besides being latent and actual, poverty is a socio-economic disease that is not only experienced by developing countries but also in developed countries. This research uses a quantitative research type. This research was conducted in East Java Province using East Java BPS data. While the data collection method uses BPS data and articles related to research that is almost the same as this study. The variables used in this study are Minimum Wage (X1), Unemployment Rate (X2), and Total Poverty (Y). Analysis of the data used in this study is Multiple Linear Regression with a significant level of 5%. The results showed that partially Minimum Wage (X1) with a significant level of 0.004 and Total Unemployment (X2) with a significant level of 0.237, the minimum wage affects the poverty variable (Y) significantly. While partially the number of unemployed variables (X2) with a significant level of 0.237, the number of unemployed does not affect the poverty variable (Y). Furthermore, the variables (X1) and (X2) simultaneously affect the poverty variable (Y)